A Cross-sectional Investigation of Gastroenteritis Inflicted by Salmonella Typhi, Entamoebahistolytica and Giardia lamblia in Karachi, Pakistan - Muhammad Salman Rasool, Wajahat Hussain Shah, Agha Asad Noor, Kauser Siddiqui, Akhtar Hussain Shar, Nadir Ali Rind, Qura-Tul-Ain, Piar Ali Shar, Sohail Ahmed Otho, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gastroenteritis is a global health concern affecting individuals of all ages and regions. The disease is caused bacteria, viruses, and parasites, and is characterized by symptoms such as diarrhea, abdominal pain, and nausea. Salmonella Typhi, Entamoeba histolytica, and Giardia lamblia are three prevalent pathogens worldwide responsible for causing gastroenteritis. Aim: To provide valuable insights into the prevalence, burden, and symptomatology of gastroenteritis caused by S. Typhi, E. histolytica, and G. lamblia in various areas of Karachi. Methods: To gather data, official registers of hospital wards, outpatient departments (OPDs), and relevant diagnostic laboratories were consulted. Stool microscopy, blood culture, Typhi Dot, and/or Widal tests were performed and their results recorded. The study collected data from a total of 1029 patients. Results: The frequency gastroenteritis rates (including cases of Typhoid, Amoebiasis, and Giardiasis), Typhoid fever, Amoebiasis, and Giardiasis were found as 71%, 57%, 30%, and 13% respectively. Conclusions: Based on the findings, the most common symptom in Typhoid cases was fever, followed by headache and abdominal pain. In Giardiasis and Amoebiasis cases, pain in abdomin was the most frequently reported symptom. By understanding the epidemiology of gastroenteritis caused by these agents, this research will add to the advancement of effective public health approaches to prevent and control gastroenteritis outbreaks in the future. Keywords: Gastroenteritis, Typhoid, Amoebiasis, Giradiasis, Salmonella Typhi, Entamoeba histolytica, Giardia lamblia